ABOUT MEASURES FOR PREVENTION OF «ATYPICAL PNEUMONIA» IMPORTATION AND DISSEMINATION AT TYUMENSKAYA PROVINCE - Yu. V. Ustyuzhanin; A. A. Ogurtsov; V. V. Cheremnykh (Acta Biomedica Scientifica, 2020)
A list of organizing and preventive measures to prevent «atypical pneumonia» delivery and dissemination atTyumenskaya Province at the period of its world epidemic is represented.